2021
DOI: 10.1016/j.jssr.2020.04.003
|View full text |Cite
|
Sign up to set email alerts
|

‘This is Me’: Expressions of Intersecting Identity in an Lgbtq+ Ethnic Studies Course

Abstract: This case study considers how one public high school in Northern California offered a yearlong course that combined a semester-long LGBTQ+ studies class with a semester-long ethnic studies class, taught by the same teacher and attended by the same cohort of 26 students. Through a combination of identity maps, student interviews, and a transfer task (i.e., a digital textbook project), we explored students’ experiences and efforts to discern how their awareness of LGBTQ+ and ethnic studies issues, particularly t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Social dynamics have also influenced the recognition of non-traditional rights in the labor context, including the rights of LGBTQ+ and informal workers. This reflects an increasingly inclusive view of fairness in employment relations (Moorhead & Jimenez, 2021).…”
Section: The Effect Of Post-modern On the Implementation Of Justice I...mentioning
confidence: 96%
“…Social dynamics have also influenced the recognition of non-traditional rights in the labor context, including the rights of LGBTQ+ and informal workers. This reflects an increasingly inclusive view of fairness in employment relations (Moorhead & Jimenez, 2021).…”
Section: The Effect Of Post-modern On the Implementation Of Justice I...mentioning
confidence: 96%
“…Indeed, as Thornton (2003) noted, “few social studies materials appear to have a substantive treatment of gay history and issues … It is as if the millions of gay inhabitants of the United States, past and present, did not exist” (p. 87). Although work has, for example, taken up issues of homophobia in the high school civics class (Marchman, 2002), traced expressions of identity in an interdisciplinary LGBTQ + inclusive ethnic studies course (Moorhead & Jimenez, 2020), or analyzed the very structures that reinforce gender inequality (Crocco, 2001), the primary means through which queer-inclusive topics are discussed are either through legislative policies and seemingly controversial issues (see, for example, Beck, 2013; Hess, 2009; Journell, 2018) or the efficacy and affect of prospective and in-service educators navigating the teaching of LGBTQ + topics (Block, 2019; Brant & Tyson, 2016). And yet, the mandate of social education goes beyond the impetus to teach inclusion and embrace diversity.…”
Section: Review Of Relevant Literaturementioning
confidence: 99%
“…Beyond English language arts (ELA) in content areas such as social studies, similar limits exist. Moorhead and Jimenez (2021) point out that “over the last decade, social studies education researchers reported very minimal progress incorporating LGBTQ+ people and their experiences into social studies curriculum” (p. 39), and Wargo (2022) notes that the few research reports documenting inclusion in social studies contexts rely on either controversial issue framings (Beck, 2013) or the efficacy of pre- and in-service teachers (Brant and Tyson, 2016), revealing little about youth experiences. Most studies focused on queer and trans youth engaging with representations of sexual and gender diversity occurred in contexts beyond classrooms such as afterschool programs (Storm and Jones, 2021), online platforms (Wargo, 2017), public streets (Cruz, 2013), school clubs (Johnson, 2017) or queer youth centers (Blackburn, 2012).…”
Section: Introductionmentioning
confidence: 99%